The most prominent threats to the thinking of Saudi youth and ways to overcome them - Hamdi, Mohammed bin Hassan Mashhour (Journal of Humanities & Social Sciences, 2017)
The study deals with the subject of threats to the Saudis youth thinking and the good ways to overcome them. The study used the analytical descriptive method, which is the most appropriate one for the nature of this study. The study showed the importance of young people to the nations, and explained that intellectual guidance influences youth thinking. It also mentioned that Westernization was a prime objective of the Western intellectual invasion, where he seeks to distract youth and others from their Islamic beliefs, and impose western values and convictions, which not serve their religion or their homelands, and mentioned that the most threatening is technical threat at this time. It also explains the most important social threats that affect the upbringing of young people such as family, friends and media. The study concluded to show how to face these threats, and what is the appropriate mechanism to overcome them and reduce the impact, and even used positively to young people from harm. And that social media is a double-weapon. It can play a positive role in influencing young people's thinking on the one hand, and it can have a negative impact on young people's thinking on the other hand. We must concentrate on the role of institutions of socialization in forming the personality of the individual from their childhood until their youth, so the institutions of socialization should play effective positive role.
Keywords: threats; thought; youth; Saudi